Reinterpretation of the Legend of Batu Gantung as the Basis for the Creation of Batak Opera, Batu Naungan Cinta - Azmi Azmi; Russel Akbar Fauzi; Tuti Rahayu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The creation of the Batak Batu Naungan Cinta Opera is an attempt to reinterpret the legend of Batu Hang as the basis for creating theatrical performances. The formal object of this creation is the theory of reinterpretation (hermeneutics) and the dialectical approach. This creation process uses the concept of performing Batak Opera combined with modern theater conventions. As the basis of creation, the theory used is the theory of montage and the technique of alliance from Bertolt Brecht. The creation methods used include: Source Studies, Visual Observations and Interviews, Literature Studies, Script Writing, Dramaturgy Design, Stage and Ensemble. The result of this process of creation is the Batak Opera performance which offers a new interpretation of the legend of the Batu Gantung.